Lessons from the past: The bale-bale as a model for sustainable and participatory public space design - Ahmadin (Research Agency for Humanity and Urban, 2025)
This article examines the role of Bale-bale in the socio-historical landscape of various rural communities in Indonesia. Beyond its basic function as a place of rest, this traditional pavilion is discussed through a sociological paradigm in the context of public spaces that played a vital role in the dialectic of communal life in the past. This study uses qualitative methods through historical and ethnographic literature reviews, which aim to reveal the dynamics of the Bale-bale as a multifunctional space. The results show that historically, the Bale-bale facilitated daily social interactions, served as a vehicle for information and deliberation, was a center of economic activity, and was a space for cultural practices such as the transmission of local knowledge and values. Its open and accessible architectural design represents the principles of togetherness, mutual cooperation, and transparency. Learning from the past, the role of the social institution known as Bale-bale can be reflected upon in the modern era to provide a perspective on the value of conceptualizing participatory and sustainable public spaceshome